PEMANFAATAN KEMASAN AKTIF MENGGUNAKAN KARAGENAN DAN EKSTRAK LIMBAH KULIT KOPI CASCARA UNTUK MEMPERPANJANG MASA SIMPAN BAKSO DAGING SAPI - meisela, anggi (STOCK Peternakan, 2023)
Beef meatballs, being a product derived from beef, exhibit a significant protein content along with a substantial water content. However, this composition renders them vulnerable to spoilage, leading to a relatively short shelf life. To address this limitation, the preservation of meatballs often involves the addition of borax, aiming to extend their storage duration. As a result, the need for a safe and practical method arises, such as the application of edible coating. The objective of this research is to examine the influence of incorporating different concentrations of coffee cascara extract as an antimicrobial compound in active edible coatings, specifically applied to beef meatball products. The study seeks to assess the microbiological properties through well diffusion testing, as well as to evaluate pH, water content, and Total plate count (TPC) of the coated meatball samples. Beef meatballs are made from beef with the addition of coffee cascara extract in three different concentrations (0%, 3%, and 6%). All treatments were then incubated at room temperature (approximately 27˚C) for varying durations (0 hours, 5 hours, and 10 hours). The method used in this study was a 3x3 factorial experiment with a Completely Randomized Design (CRD) and 3 replications. The data obtained were analyzed using analysis of variance, and if the treatments had a significant effect (P 0.05), they were further tested using Duncan Multiple Range Test (DMRT). The research results revealed that the addition of coffee cascara extract had a significant effect (P 0.05) on the decrease of pH and total plate count, as well as an increase in water content. The storage time significantly influenced (P 0.05) the reduction of water content, as well as the increase in pH value and total plate count. The interaction between the addition of coffee cascara extract and the incubation time did not exhibit significant differences (P 0.05) concerning pH value, water content, and total plate count.